A mixture of diethylhexyl, diisononyl and dibutyl phthalate decreased anogenital distance, postnatal testosterone levels, and changed social behavior in Wistar rats - Morová, M; Senko, T; Olexová, L; Dzirbíková, Z; Kršková, L (Physiological research, 2020)
Phthalates are chemicals interfering with the function of testosterone and are suspected to play a role in the emergence of neurodevelopmental diseases. This could be due to interference with brain development for which optimal testosterone levels are essential. We investigated the effect of prenatal and early postnatal exposure to a phthalate mixture on the anogenital distance (AGD), plasma testosterone levels and social behavior in rats. Pregnant rats were exposed to a mixture of diethylhexyl, diisononyl and dibutyl phthalate, each at a dose of 4.5 mg/kg/day, from gestational day 15 to postnatal day 4. A social interaction test was performed to assess sociability in the three ontogenetic stages (weaning, puberty, adulthood). AGD was measured in adulthood to assess changes in prenatal testosterone levels. Plasma testosterone levels were measured in adults by a radioimmunoassay. The total frequency and time of socio-cohesive interactions were decreased in phthalate exposed females in weaning, puberty and adulthood. Phthalate exposed males showed a decrease in the frequency of social interactions in weaning only. Shorter anogenital distance was observed in adult males exposed to phthalates. Decreased testosterone levels were observed in the exposed group in both sexes. Our results suggest that early developmental phthalate exposure may play an important role in the hormonal and behavioral changes associated with several neurodevelopmental diseases.
Keywords: novorozená zvířata; potkani Wistar; Testosterone; Social Behavior; matka - expozice noxám; Dibutyl Phthalate; zvířata; Male; Female; Genitalia; pohlavní orgány; těhotenství; Plasticizers; Prenatal Exposure Delayed Effects; kyseliny ftalové; Maternal Exposure; Animals; Diethylhexyl Phthalate; mužské pohlaví; krysa rodu Rattus; Rats; Rats, Wistar; ženské pohlaví; Animals, Newborn; diethylhexylftalát; Pregnancy; sociální chování; dibutylftalát; pohlavní dospělost; testosteron; zpožděný efekt prenatální expozice; změkčovadla; Sexual Maturation; Phthalic Acids